Memory and ancestrality: traces that echo and spread in contemporaneity - Vaneau, Célia Regina Gouvêa (Sala Preta, 2016)
This article proposes a reflection about the transformation of parameters, when the predominance of the conceptual procedure gives way to the emergence of memory, or to what is inscribed on the body. It questions the existence of preserved cultural centers and avoids the duality between central and peripheral. From events observed in certain regions of Brazil, it finds the fertile way of ancestrality, which is present in multiple instances of artistic production. The arguments are supported, among others, by the thought of the theater directors Jerzy Grotowski and Peter Brook, theorists Henri Bergson and Walter Benjamin and neuroscientist Antonio Damasio.